Tekmovanje za Cankarjevo priznanje: zasnova, cilji, vprašanja - Saksida, Igor (Revija za elementarno izobraževanje, 2011)
The Cankar Award Contest : Framework, Goals, Questions. The article discusses an optional form of reading competence assessment (called the Cankar Award contest). In the introduction, it presents some changes in the organisation of the respective contest, its purpose and goals, underlining the significance of mentors’ participation. The role of the latter is to inform pupils about specific demands of the contest, as well as to prepare them for it. In the main body, the article discusses in detail the differences between spontaneous reading, and more critical, in-depth or literary reading – the latter goes beyond fractional and subjective responses based on the dialog between a teacher (as an authority) and pupils, and through development of reading strategies that include literary and broader knowledge. In addition, the article provides commentary on the achievements of Slovenian pupils as shown by PISA 2009, and concludes the discussion by demonstrating a variety of texts and reading tasks used in the Cankar Award contest, stressing the importance of professional autonomy in the selection of both texts and tasks.
Keywords: the Cankar Award contest; types of reading; reading competence assessment; PISA 2009; selection of texts and reading tasks